Application of proanthocyanidin in the treatment and repair of deep caries - GAO Ying; WANG Jue; TAO Lu; YAO Jingjing; YU Jinling; HUANG Handan; YANG Liuqing; LIU Zhihui (口腔疾病防治, 2023)
Proanthocyanidin (PA), as a kind of natural plant polyphenol, have a variety of biological functions, such as promoting remineralization, inducing collagen cross-linking, inhibiting protease activity and inhibiting bacteria. Therefore, PA could be broadly used in the clinical application of treatment and repair of deep caries in the future; for example, PA could promote dentin remineralization, improve resin-dentin bonding durability and improve the dentin acid erosion effect. This application potential of PA arises from several features, firstly, PA can not only promote dentin remineralization on its own or with other remineralizers but also exhibits antibacterial effects, which can inhibit acid production while reducing the formation of cariogenic pathogens and their biofilms. Based on the above features, PA can reduce the incidence of caries disease; thus, PA improves deep caries and long-term effects after treatment. In addition, PA added to adhesives or etch agents can improve the etching and bonding effect of dentin by inducing collagen cross-linking and inhibiting protease activity, thus achieving the ultimate goal of improving the bonding performance of deep caries. This paper summarizes recent progress of research on PA for the treatment and repair of deep caries, including the promotion of dentin remineralization and antibacterial activity as well as the improvement in dentin bonding and acid etching effect, to provide a more comprehensive reference for treating and restoring deep caries in clinical practice.